Analisis Kemampuan Mahasiswa Dalam Pengunaan Kecerdasan Buatan (Ai) Pada Penulisan Karya Tulis Ilmiah Mahasiswa Di Lingkungan STKIP Pesisir Selatan - Riska Mayeni; Revi Handayani; Risma Wiwita (JURNAL ARMADA PENDIDIKAN, 2025)
The development of artificial intelligence (AI) has influenced the practice of scientific writing in higher education. This study aims to analyze students' ability to use AI in scientific writing at STKIP Pesisir Selatan, including the level of utilization, operational and evaluative skills, the role of supervisors, and its impact on writing quality. The study employed a qualitative approach with a case study method. Data were collected through questionnaires, interviews, and document analysis of student writing, then analyzed using reduction, categorization, and thematic meaning extraction techniques. The results indicate that most students have utilized AI to generate ideas, develop outlines, paraphrase, and improve grammar. While operational skills in using AI are generally good, evaluation skills, source verification, and understanding of ethical use are still limited. The use of guided AI contributes to the structural and linguistic clarity of writing, but does not automatically increase the depth of analysis. The role of supervisors is crucial in guiding the appropriate and responsible use of AI. This study confirms that AI is effective as a scientific writing aid when combined with digital literacy, critical thinking skills, and clear academic ethical guidelines.